Epigallocatechin-3-Gallate-Loaded Gold Nanoparticles: Preparation and Evaluation of Anticancer Efficacy in Ehrlich Tumor-Bearing Mice - Mohamed A. Safwat; Bothaina A. Kandil; Mohamed A. Elblbesy; Ghareb M. Soliman; Nermin E. Eleraky (MDPI AG, 2020)
Epigallocatechin-3-gallate (EGCG) is a pleiotropic compound with anticancer, anti-inflammatory, and antioxidant properties. To enhance EGCG anticancer efficacy, it was loaded onto gold nanoparticles (GNPs). EGCG-GNPs were prepared by a simple green synthesis method and were evaluated using different techniques. Hemocompatibility with human blood and in vivo anticancer efficacy in Ehrlich ascites carcinoma-bearing mice were evaluated. EGCG/gold chloride molar ratio had a marked effect on the formation and properties of EGCG-GNPs where well-dispersed spherical nanoparticles were obtained at a molar ratio not more than 0.8:1. The particle size ranged from ~26 to 610 nm. High drug encapsulation efficiency and loading capacity of ~93 and 32%, respectively were obtained. When stored at 4 °C for three months, EGCG-GNPs maintained over 90% of their drug payload and had small changes in their size and zeta potential. They were non-hemolytic and had no deleterious effects on partial thromboplastin time, prothrombin time, and complement protein C3 concentration. EGCG-GNPs had significantly better in vivo anticancer efficacy compared with pristine EGCG as evidenced by smaller tumor volume and weight and higher mice body weight. These results confirm that EGCG-GNPs could serve as an efficient delivery system for EGCG with a good potential to enhance its anticancer efficacy.